Carotid Intima–Media Thickness May Be a Useful Biomarker in Determining Early Cardiovascular Risk in Mild Autonomic Cortisol Hypersecretion - Ahmet Numan Demir; Emre Durcan; Hande Mefkure Özkaya; Özlem Haliloğlu; Fatma Ela Keskin; Pınar Kadıoğlu (Cerrahpaşa Medical Journal)
Objective: This study aimed to assess the cardiovascular risk in patients with mild autonomous cortisol hypersecretion (MACS). To this end, the suitability of carotid intima–media thickness (cIMT) as a surrogate biomarker was evaluated.